Naughtiest girl wants to win - Blyton, Enid (Hodder Children's Books London, 2010)
Elizabeth is furious when a girl new to the sixth form becomes head girl over the obvious choice, her friend Emma. The new head girl, Kerry, is a young actress, and Elizabeth is convinced that all the seniors have been swayed by her acting skills, both on screen and at school. She knows the real Kerry is a nasty piece of work - but how can she prove it? She's determined to try and starts a campaign to replace Kerry with Emma. But Kerry is cleverer than Elizabeth thinks, and somehow she just manages to make the Naughtiest Girl look like a troublemaker!